HASIL BELAJAR KETERAMPILAN MENULIS BAHASA JERMAN SISWA KELAS XI IPS 2 SMAN 1 KAMAL DENGAN MENGGUNAKAN PUZZLE - SUGIHARSIH, ANITA (LATERNE, 2014)
Abstract Writing is one of four German language skills are taught in high school. In learning these skills is well aligned with each other, therefore all four of them to be executed sequentially and systematically. Writing skills are categorized into skills that are productive and complex. Students as learners are required to ideas, thoughts and opinions himself with good language and precise, especially in learning, especially learning the German language learners are required to master vocabulary, spelling, word order in sentences, and grammatiknya. Jung (1992:12) says that "Schreiben ist eine h?chst komplexte Fertigkeit, die eine sprachliche gedankliche T?tigkeit bei und im Bereich des gleichzeitigen Kenntnis Wortschatzes, Grammatik der, der Textkonstruktion und dem Bereich jeweiligen thematischen verlangt". To facilitate the students practice writing the required media. For the study Media in used, namely the puzzle media. The process is a writing exercise based on a picture puzzle was neatly organized which allows students to build knowledge in their own language. Working with images can stimulate the minds of students to move into a visual description of coherent writing. Removal process is what will mestimulasi memory of students in learning the material received. The problems of this research is how the learning outcomes of students’ writing skills XI IPS 2 SMAN 1 Kamal after using media puzzle. This study aimed to describe the learning outcomes of students’ writing skills XI IPS 2 SMAN 1 Kamal after using media puzzle. The results of this quantitative study is indicated by the data pre-test and post-test. From the results it can be concluded that the results of learning writing skills Siwa XI IPS 2 SMAN 1 Kamal after using media puzzle fall into either category with an average value of 76.83. This value increased 18.87 points from pre-test values ??are categorized quite well. Keywords: learning, writing skills, media puzzle